IDENTIFICATION OF ANISAKID NEMATODE L3 LARVAE INFECTION ON SKIPJACK TUNA (KATSUWONUS PELAMIS L.) FROM KUPANG WATERS, EAST NUSA TENGGARA OF INDONESIA - Haryadi L.; Suprayitno E.; Aulanni’am A.; Amin M.; Hariati A.M. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
The larvae of Anisakis were living parasites and made marine mammals, birds and reptiles the definitive host. Identification of Anisakis larvae using morphological observation methods will be difficult, especially if there are only a few samples that can be identified. PCR is an identification method using DNA from a small sample quantity and can provide DNA sequence samples. This study aimed to determine the type and infection level of Anisakis sp. at skipjack tuna (Katsuwonus pelamis) from the Oeba Fish Auction (TPI) Kupang City morphologically and molecularly. Morphological analysis results of 30 Anisakis larvae showed the body parts of Anisakis larvae, namely the head, digestive tract, and tail. The infection of Anisakis nematodes in skipjack tuna found five individual nematodes in muscle tissue, 59 individuals in stomach tissue, and 1991 individuals in internal organs. Alignment results between isolates At1 and At2 against isolates A. typica comparing (outgroup), isolate At1 and At2 have high homologs. Based on the results of the study concluded that the type I Anisakis isolated from skipjack tuna (Savu Sea) was Anisakis typica.